2021
DOI: 10.1126/scirobotics.abc5044
|View full text |Cite
|
Sign up to set email alerts
|

Mutual gaze with a robot affects human neural activity and delays decision-making processes

Abstract: Task-irrelevant robot gaze evokes neural suppression, delays decisions, and alters social decision-making strategies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 58 publications
(99 reference statements)
1
22
0
Order By: Relevance
“…Instead, our findings support the idea that the effect related to (in)congruency of social cues and social feedback was driven by the expectations of consistency between the cue and the feedback communicated by the robot. The violation of such expectation may have led to engagement of cognitive processes related to reasoning about the robot's actions and intentions, or to a higher effort needed to suppress the cued response it has become evident that it is in contradiction with the feedback, most of the time (see similar results by Belkaid et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Instead, our findings support the idea that the effect related to (in)congruency of social cues and social feedback was driven by the expectations of consistency between the cue and the feedback communicated by the robot. The violation of such expectation may have led to engagement of cognitive processes related to reasoning about the robot's actions and intentions, or to a higher effort needed to suppress the cued response it has become evident that it is in contradiction with the feedback, most of the time (see similar results by Belkaid et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…Some studies specifically focused on replicating the gaze cueing paradigm using an embodied robot (Kompatsiari et al, 2019(Kompatsiari et al, , 2021. Moreover, eye contact with a robot prior to decisionmaking has been shown to delay decisions, affect neural activity and influence strategies in a competitive game (Belkaid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the distracting effect of gaze cues was prolonged in time even when the stimulus onset asynchrony was equal to 1s ( Kompatsiari et al, 2021b ). Using a decision-making task Belkaid et al, ( 2021 ) showed that mutual gaze delayed reaction times by increasing the decision threshold. Also, iCub’s mutual gaze was associated with higher alpha synchronization in the EEG signal, indicating that during mutual gaze with the robot, suppression mechanisms were activated.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the distracting effect of gaze cues was prolonged in time even when the stimulus onset asynchrony was equal to 1s (Kompatsiari et al, 2021b). Using a decision-making task Belkaid et al, (2021) showed that mutual gaze Robot's social gaze affects conflict resolution 21 delayed reaction times by increasing the decision threshold. Also, iCub's mutual gaze was associated with higher alpha synchronization in the EEG signal, indicating that during mutual gaze with the robot, suppression mechanisms were activated.…”
Section: Discussionmentioning
confidence: 99%